Peculiarities of electron microscopic hippocampal formation development characteristics in posterity of rats after PgE2 injection for labor induction - Hryhorieva, O. A.; Mamay, I. Yu.; Tertyshniy, S.; Dariy, V. I.; Guminskyv, Y. Y.; Григор'єва, Олена Анатоліївна; Мамай, Ірина Юріївна; Тертишний, Сергій Ігорович; Дарій, Володимир Іванович (My University, 2022)
The aim: To determine the peculiarities of electron microscopic hippocampal formation development characteristics in postetry of rats during two first weeks of postnatal life after intravaginal injection of prostaglandin E2 for labor induction. Materials and methods: The ultrastructural changes of hippocampal formation in posterity of white syngenic rats at the 1st, 7th and 14th days of postnatal life were examined. In this study we used electron-microscopic method. Brain tissue from experimental animals underwent standart stages necessary for electron microscopy and poured into pure Epon. Epon polymerization was carried out in two stages at 36 ° C (12 h) and 56 ° C (24 h). Ultrathin (50-60 nm) sections were obtained on a PowerTome RMC Boeckeler ultratome and then contrasted according to the E. Reynolds method. Ultrathin sections were studied in a PEM-100 electron microscope with an accelerating voltage 60 kV. Results: Based on the obtained data in the study of the hippocampal formation in postery of rats after induction of labor, analysis of the literature devoted to the electron microscopic study of the brain after ischemic injuries, it can be concluded that on the background of stimulation of labor by PgE2, changes corresponding to ischemic damage take place in the rat brain. Conclusions: In posterity of rats after receiving PgE2 for labour induction it was revealed microcirculatory changes; edema of the presynaptic endings, synaptic vesicles aggregation in the center of the presynaptic processes, swelling and destruction of mitochondria; oligodendroglia changes; ultrastructural changes in neurons like edema and vacuolization of mitochondria.
O. A. Hryhorieva - ORCID: 0000-0002-6101-8322A; I. Yu. Mamay - ORCID: 0000-0002-1437-8106B; S. Tertyshniy - ORCID: 0000-0003-3856-4234; V. I. Dariy - ORCID: 0000-0001-9074-6911
Keywords: hippocampal formation; oligodendroglia; synaptic apparatus; neurons; prostaglandin E2